Unveiling the Hidden Networks: AFM Insights into Pre‐Vulcanized Hevea Latex and Its Profound Impact on Latex Film Mechanical Properties - Narueporn Payungwong; Ken Nakajima; Chee‐Cheong Ho; Jitladda Sakdapipanich (Macromolecular Materials and Engineering)
Abstract Natural rubber (NR) films with different natural networks—concentrated NR (CNR), deproteinized NR (DPNR), and small rubber particles (SRP)—are investigated to explore the relationship between network structure and film properties using atomic force microscopy (AFM) in PeakForce Quantitative Nanomechanics (QNM) mode. Nitrogen content, gel content, and particle size distribution analyses reveal distinct network topologies in each latex type. Mechanical testing shows variations in tensile strength and crosslink density. AFM analysis provides insights into the crosslink network structures within the pre‐vulcanized latex film. It is found that DPNR and CNR films have a uniform distribution of crosslink networks, with DPNR exhibiting higher Young's modulus values. In contrast, SRP shows varying Young's modulus values, suggesting poor coalescence arising from a harder particle surface and a softer rubber core in an inhomogeneous network structure intrinsic to the non‐rubber components (NRCs) make‐up of SRP latex. This study highlights the pivotal role of natural network structures formed by NRCs in determining the ultimate properties of latex films, which has significant implications for the rubber industry, particularly in the production of latex‐dipped products, medical devices, and bioengineering applications.